1998
DOI: 10.1103/physreva.58.3868
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state grating echoes from Rb vapor at room temperature

Abstract: We have used two sets of opposite circularly polarized traveling wave pulses separated in time to establish, and subsequently rephase, a spatially modulated coherence between the magnetic sublevels of the Fϭ3 ground state in Doppler broadened 85 Rb vapor. The rephasing results in a magnetic grating echo whose duration is an accurate measure of the velocity distribution. We demonstrate that the time scale of the experiment is determined solely by the transit time of atoms across the laser beam. The shortening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It was recently shown that coherence among ground state Zeeman sublevels of Rb atoms can be used for detection of a perturbed ͑Ar͒ in an atomic cell. 6 In this experiment, the cross section for Rb-Ar velocity-changing collisions was inferred from properties of coherence grating echoes. 7 However, photon echoes are essentially transient phenomena with a complicated experimental implementation.…”
mentioning
confidence: 99%
“…It was recently shown that coherence among ground state Zeeman sublevels of Rb atoms can be used for detection of a perturbed ͑Ar͒ in an atomic cell. 6 In this experiment, the cross section for Rb-Ar velocity-changing collisions was inferred from properties of coherence grating echoes. 7 However, photon echoes are essentially transient phenomena with a complicated experimental implementation.…”
mentioning
confidence: 99%
“…This is analogous to the reversal of the Doppler phases of individual atoms in a traditional two-pulse photon echo experiment [150] that can be used for measuring the excited state lifetime [151]. In the absence of decoherence due to collisions and background light, the MGE amplitude should decay on a time scale determined by the transit time of atoms through the laser beams [149].…”
Section: Magnetic Coherencesmentioning
confidence: 95%
“…A magnetic grating echo (MGE) is observed using a second set of excitation pulses at t = T to rephase the coherence grating, as in Fig. 14(c) [147][148][149]. The second pulse modifies the time-dependent coefficients that describe the coherent superposition of magnetic sublevels so that the grating reforms at t = 2T.…”
Section: Magnetic Coherencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal scattered from this coherence grating will have the same time constant as for the case of perpendicular linear polarizations. The dephasing time of the grating has been used to measure the velocity distributions of warm vapor [31,32], cold atomic gases [32,33], and atomic beams [34].…”
Section: Population and Coherence Magnetometrymentioning
confidence: 99%